2014
DOI: 10.1016/j.ijpvp.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Bree problem with different yield stresses on-load and off-load and application to creep ratcheting

Abstract: The ratchet boundaries and ratchet strains are derived for the Bree problem and an elastic perfectly plastic material with different yield stresses on-load and off-load. The Bree problem consists of a constant uniaxial primary membrane stress and a cycling thermal bending stress. The ratchet problem with differing yield stresses is also solved for a modified loading in which both the primary membrane and thermal bending stresses cycle in-phase. The analytic solutions for the ratchet boundaries are compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…31,32 Most engineering components are in fact subjected to creep and ratcheting interaction, suffering more damage than under creep or ratcheting alone. 33,34 This makes the ratcheting phenomenon more complicated. Their synergetic effect challenges structural integrity and operating safety of pressure vessels.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Most engineering components are in fact subjected to creep and ratcheting interaction, suffering more damage than under creep or ratcheting alone. 33,34 This makes the ratcheting phenomenon more complicated. Their synergetic effect challenges structural integrity and operating safety of pressure vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The Bree problem is a typical benchmark example for uniaxial shakedown and ratchet analysis of structure under thermomechanical loading. Some authors (Bree, 1967;Bradford et al, 2014) have studied the shakedown boundary considering the effect of mean temperature on yield strength analytically. In these analyses, the elastoplastic material with different yield strengths off-load and on-load is considered, and the temperature gradient across can wall is small enough thus the yield stress is uniform over the whole structure.…”
Section: Verification Of the Methods For Plane Stress Element By The Bmentioning
confidence: 99%
“…Two dimensional problem and the Poisson's effect were also considered by the author and it was concluded that the ASME design code is conservative. Bradford et al carried the studies over Bree diagram with different values of yield stress during on-load and off-load [5]. The temperature dependence of yield stress was taken into account and off-load (no thermal load) yield stress was assumed to be greater than the on-load yield stress.…”
Section: Introductionmentioning
confidence: 99%